2016
DOI: 10.3390/nu8110669
|View full text |Cite
|
Sign up to set email alerts
|

Serum Retinol Levels in Pregnant Adolescents and Their Relationship with Habitual Food Intake, Infection and Obstetric, Nutritional and Socioeconomic Variables

Abstract: Globally, vitamin A deficiency (VAD) affects about 19.1 million pregnant women. Its occurrence is classically associated with inadequate food intake and may also be associated with socioeconomic factors and the presence of infection. The aim of this study was to determine the factors related to serum retinol levels among pregnant teenagers. The sample consisted of 89 pregnant adolescents, from whom socioeconomic, obstetric, anthropometric, and food consumption data were collected. Serum concentrations of retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Other studies have shown similar results, reporting vitamin A deficiency to be more common at the end of pregnancy than at the beginning [18,30,31,35,37,52]. These findings could be explained by the increase in the maternal-fetal transfer of vitamin A due to faster fetal growth towards the end of pregnancy [53].…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Other studies have shown similar results, reporting vitamin A deficiency to be more common at the end of pregnancy than at the beginning [18,30,31,35,37,52]. These findings could be explained by the increase in the maternal-fetal transfer of vitamin A due to faster fetal growth towards the end of pregnancy [53].…”
Section: Discussionsupporting
confidence: 56%
“…Consequently, the prevalence of VAD in the group of women with more than 12 years of schooling was lower. Conversely, in other studies such as that conducted to evaluate VAD in pregnant adolescents in Piauí [37] and another carried out to assess mothers in the state of Pernambuco [41], no statistically significant association was found between VAD and schooling. A fact that needs to be taken into account refers to the rapid nutritional transition occurring in Brazil that differentiates this country from others.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…A study conducted in Brazil investigated the relationship between serum retinol concentrations with dietary intake, socioeconomic status, obstetrics factors, nutrition status, and presence of infection in pregnant adolescents found VAD (retinol <0.70 μmol/L) in 34.8% of women. The mean ± SD retinol concentration was 0.92 ± 0.42 μmol/L, indicating the existence of a serious public health problem in this young population [21]. A second Brazilian study, conducted at a public maternity hospital in Recife, examined the serum retinol concentrations of 65 consecutive mother-newborn pairs at delivery from January to August 2008.…”
Section: Discussionmentioning
confidence: 99%